Pengaruh Kepemimpinan yang Melayani, Kompensasi, dan Motivasi Terhadap OCB Pada PT Semen Gresik di Kabupaten Rembang (Studi Kasus Departemen Sumberdaya Manusia) - Priyono Priyono; Gunawarman Gunawarman (Jurnal Mirai Management, 2022)
Events or incidents that exist in the human resources department at PT. Semen Gresik can be said that the level of work owned by each employee who has not yet been formed is caused by the low initiative that has individual characteristics or more of oneself, causing problems that are not conducive. The organization can certainly run well and conducive if the leader can serve and understand the character of each employee, with the compensation given by the leadership to employees, all members in the organization will work in totality because compensation can motivate employees to work optimally. This study aims (1) to examine and analyze the influence of servant leadership on organizational citizenship behavior, (2) to examine and analyze the effect of compensation on organizational citizenship behavior, (3) to examine the influence of motivation on organizational citizenship behavior. This type of research is qualitative, with the research location at PT. Semen Gresik human resources department. This research was conducted using total sampling because the population in the human resources department is relatively small, amounting to 35 people. To determine the validity of the instrument used validity and reliability tests. The data analysis method used is multiple linear regression analysis. Based on the analysis, it is known that: (1) Servant Leadership has a positive and significant effect on Organizational Citizenship Behavior, (2) Compensation has a positive and significant effect on Organizational Citizenship Behavior, (3). Motivation has a positive and significant effect on Organization Citizenship Behavior Keywords: Kepemimpinan yang Melayani, Kompensasi, Motivasi, Organization Citizenship Behaviour